A supervisão escolar em Goiás - Bernardes, Maria Paulina Arantes (2016)
Submitted by Kelly Ayala (kelly.ayala@fgv.br) on 2016-06-06T12:15:45Z No. of bitstreams: 1 000049040.pdf: 9775913 bytes, checksum: f49cee9c2a559271effca75efafc5bf4 (MD5) === Made available in DSpace on 2016-06-06T12:16:17Z (GMT). No. of bitstreams: 1 000049040.pdf: 9775913 bytes, checksum: f49cee9c2a559271effca75efafc5bf4 (MD5) Previous issue date: 1983-04-28 === This research is about the beginning of school education Supervision in Brazil, that started with the North-American penetration in Brazilian education, adopting a program of technical assistance and also a post-war financial help to Brazil. The Brazilian-American Assistance program to Elementary Teaching (PABAEE) was analyzed as it is one of a kind of those programs and the rising of Brazilian school Supervision was analyzed too. After having established the beginning of Brazilian Supervision, we studied School Supervision in Goiás, that was unstained in the CTM of Inhumas and a new Institutional piece was widowed to it after the 5.540/68 law. We made a comparison between Inhumas Supervision and University and finally we discussed about the place and the task that should be developed by the Supervisor in nowadays Brazilian educational system. === O presente estudo trata das origens da Supervisão Escolar no Brasil, marcada pela penetração norte-americana na educação brasileira, através da implementação dos programas de assistência técnica e ajuda financeira ao Brasil no pós-guerra. Analisou-se o Programa de Assistência Brasileiro-Americana ao Ensino Elementar (PABAEE) como um destes programas e de onde surgiu a Supervisão Escolar Brasileira. Definida a origem da Supervisão brasileira, analisou-se a Supervisão Escolar em Goiás, instalada no CTM de Inhumas e definida em nova situação institucional após a lei 5.540. Comparou-se a formação do Supervisão de Inhumas e da Universidade, e discutiu-se, para finalizar, qual o espaço e qual a tarefa do Supervisor no sistema educacional brasileiro hoje.